2019
DOI: 10.1002/slct.201903071
|View full text |Cite
|
Sign up to set email alerts
|

Designing of Ultrafine PdNPs Immobilized Pyridinic‐NDoped Carbon and Evaluation of its Catalytic Potential for Konevenagel Condensation, Synthesis of 4H‐pyran Derivatives and Nitroreduction

Abstract: We report the desiging of ultrafine Pd‐based nanocatalyst containing N‐doped carbon structure (Pd@NC). The material was prepared by direct dehydration at 120 °C followed by mixing and heating with a dopant (ammonium oxalate) at 150 °C in a furnace. The Pd@NC nanocatalyst containing electron‐rich pyridinic‐N doped carbon structure, was thoroughly characterized by various techniques namely SEM, EDX, TEM, FTIR, ICP‐AES, XRD, XPS, TGA and Raman spectroscopy. The utility of the Pd@NC nanocatalyst was explored for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…38 The peak around 261 represents the graphitic carbon, which has been diffracted from the (002) plane. 39,40 The size of Pd@NGO can be calculated using the Debye-Scherrer equation shown as:…”
Section: Resultsmentioning
confidence: 99%
“…38 The peak around 261 represents the graphitic carbon, which has been diffracted from the (002) plane. 39,40 The size of Pd@NGO can be calculated using the Debye-Scherrer equation shown as:…”
Section: Resultsmentioning
confidence: 99%
“…Gupta and coworkers disclosed an environmentally benign and simple procedure for the preparation of Pd nanocatalyst containing pyridinic‐ N doped carbon structure (Pd@NC) through dehydration of maltose in the attendance of H 2 SO 4 , heating with ammonium oxalate at 150 °C, and followed by the deposition of Pd NPs that were synthesized by the reduction of palladium acetate (Figure 77). [38b] The Pd@NC catalytic potential was evaluated for Konevenagel condensation (Scheme 119), synthesis of 4 H‐ pyran derivatives, the reduction of nitro compounds as well as oxidation of 5‐hydroxymethylfurfural. It has been found that excellent catalytic activity mainly resulted from the metal‐support interaction between Pd NPs and pyridinic‐ N dopant on the carbon structure.…”
Section: Heteroatom‐doped Porous Carbon/metal Catalystsmentioning
confidence: 99%
“…no., 504-29-0; structure, Figure ) is widely employed in a variety of applications of pharmaceuticals’ synthesis, especially for antihistamines, antiflammatories, and other drugs. , Brominated 2-aminopyridine attracted considerable attention for its applications as useful intermediates or building blocks for pharmaceuticals. In particular, 2-aminopyridine also serves as an useful raw material for some liquid crystals. , Regardless of its wide applications, there has been little research into the thermodynamic properties of 2-aminopyridine in neat and mixed solvents. 2-Aminopyridine is generally obtained through the reduction of 2-nitropyridine or 2-halopyridine in various solvents such as ethanol, , methanol, acetonitrile, N -methyl-2-pyrrolidine (NMP), and so on. Therefore the solubility of 2-aminopyridine in various solvents has a significant impact on product yield.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Regardless of its wide applications, there has been little research into the thermodynamic properties of 2-aminopyridine in neat and mixed solvents. 2-Aminopyridine is generally obtained through the reduction of 2-nitropyridine or 2-halopyridine in various solvents such as ethanol, 12,13 methanol, 14 acetonitrile, 15 Nmethyl-2-pyrrolidine (NMP), 16 and so on. Therefore the solubility of 2-aminopyridine in various solvents has a significant impact on product yield.…”
Section: ■ Introductionmentioning
confidence: 99%